Anti-inflammatory therapy of acute rhinosinusitis using ketoprofen lysine salt - S. V. Ryazantsev (Медицинский совет, 2015)
Inflammatory diseases of the paranasal sinuses are one of the most actual problems of modern otorhinolaryngology. Statistics show that one in eight people have ever suffered rhinosinusitis (13.4%). In the Russian Federation, 15 to 36% of patients admitted for treatment in ENT units are suffering from acute or chronic rhinosinusitis in the acute phase. [1] 10-20% of hospitalized patients with rhinosinusitis are in severe condition, while purulent-septic and intracranial complications are diagnosed in 3-5% of patients. [2] In several Russian regions, inpatient mortality from purulent intracranial complications of rhinosinusitis reaches 10--17%. [3]